PENGARUH TEKNIK RELAKSASI GUIDEDIMAGERY TERHADAP PENURUNAN NYERI PENDERITA GASTRITIS PADA REMAJA DI POSKESDES DESA KESAMBI KECAMATAN BANDUNG KABUPATEN TULUNGAGUNG TAHUN 2022 - Yanti, Anik Nuridayanti; Rohmah, Ristia Faktur; A.S, Wibowo Hanafi; Sutik, Sutik (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2023)
ABSTRACT Background : Gastritis is a disease that, attacks all walks of life, can also occur at a young age. Gastritis often occurs due to excessive stress due to environmental influences. Objective : this study was to determine the effect of guided imagery relaxation techniques on reducing pain in gastritis sufferers in adolescents in Kesambi Village, Bandung Tulungagung Design of this research is Pre Experiment with Pretest Posttest design. The population is teenagers in Poskesdes Kesambi Village, Bandung District, Tulungagung Regency with a sample of 22 respondents taken using accidental sampling technique. The independent variable is guided imagery relaxation technique and the dependent variable is the decrease in pain in gastritis sufferers. Data were collected using questionnaires and observation. Data expressed in ordinal scale were analyzed by Wilcoxcon test . Results : showed the effect of guided imagery relaxation techniques on reducing pain levels of gastritis sufferers in adolescents at the Kesambi Village Health Post, Bandung District, Tulungagung Regency. Conclusion : of this study is that guided imagery relaxation techniques can reduce pain levels in adolescents. It is expected that adolescents can use guided imagery relaxation techniques to overcome the problem of pain when there is a recurrence of gastritis.